Hubungan antara forgiveness dengan resiliensi pada penyintas pasca konflik di Aceh - Rifda Salsabila; Diah Karmiyati; Udi Rosida Hijrianti (Cognicia, 2019)
Conflicts of human rights violations have taken place between GAM and the Indonesian government in Aceh which have created feelings of heartache, trauma, fear and pressure, resulting in negative emotions that tend to stick to conflict survivors. To overcome the negative emotions and pressures, it is necessary to have forgiveness capabilities that can bring positive emotions as one of the submber resilience. The purpose of this study is to know the relationship between forgiveness and resilience of post-conflict survivor in Aceh. The research design used quantitative non-experimental study correlational with 2 variables. Cluster random sampling is used in term to determine the sampling method in Aceh Besar, Bireuen and Banda Aceh with participants is (N=427). Nashori (2012) and Septia (2018) with CVR scale from Reivich and Shatte (2000) are used as instrument to determine the reseratch. The data is analysed by using Pearson product moment. And the result research is there is a significant correlation between forgiveness and resilience in post-conflict survivor in Aceh.